Distribution survey of Kloss’s Gibbons (Hylobates klosii) in Mentawai Islands, Indonesia - ARIF SETIAWAN; CHRISTIAN SIMANJUNTAK; ISMAEL SAUMANUK; DAMIANUS TATEBURUK; YOAN DINATA; DARMAWAN LISWANTO; ANJAR RAFIASTANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Setiawan A, Simanjuntak C, Saumanuk I, Tateburuk D, Dinata Y, Liswanto D, Rafiastanto A. 2020. Distribution survey of Kloss’s Gibbons (Hylobates klosii) in Mentawai Islands, Indonesia. Biodiversitas 21: 2224-2232. The aim of this study was to assess the population density, distribution, habitats, and threats of Kloss’s gibbon (Hylobates klossii) in the Mentawai Islands, Indonesia. In 2011-2012 we conducted a survey on Siberut Island, outside of the National Park, as well as a short visit to Sipora, North Pagai, and South Pagai. From March to September 2017, we surveyed once again some previous localities on the Siberut and Sipora islands to keep up to date with recent developments on the ground. On Siberut we used an auditory sampling method through fixed point counts, combined with line transects, to estimate the gibbon densities. In total, 113-morning calls were recorded from 13 Listening Points; 75 of these were used for density calculations. We recorded 35 individuals based on direct sightings during 66.4 km of transect distance walked. We found 13 localities outside of Siberut National Park that still have Kloss's gibbons; densities varied between 1.04group/km2 to 4.16 group/km2. No gibbons were found and heard during the short survey in Sipora and South Pagai, though we found a group of gibbons in North Pagai. Our 2017 survey revealed massive habitat changes in South Siberut. Previously existing forest localities in South Siberut were gone due to road construction, agriculture expansion, and logging.